2021
DOI: 10.3389/feduc.2021.729027
|View full text |Cite
|
Sign up to set email alerts
|

DI (Differentiated Instruction) Does Matter! The Effects of DI on Secondary School Students’ Well-Being, Social Inclusion and Academic Self-Concept

Abstract: In consideration of the substantial increase in students’ learning demands, teachers are urged to address student heterogeneity in their daily teaching practice by means of differentiated instruction (DI). The practice of DI, as a vehicle to achieve inclusive education, not only aims to support all students’ academic learning but also foster their social and emotional development. However, current research in the field of DI has mostly been limited to an examination of its effects on students’ achievement outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…For instance, multiple studies have reported positive effects of teachers' use of DI on students' mathematics and reading achievement (Bal, 2016;Goddard et al, 2015;Reis et al, 2011). Furthermore, studies by Lindner et al (2021) and Pozas et al (2021) indicate that students' perceptions of their teachers' DI use strongly predicted students' well-being, social inclusion and academic self-concept. Likewise, DI has also been reported to foster learners' interest, motivation and self-confidence (Eysink et al, 2017;McQuarrie & McRae, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, multiple studies have reported positive effects of teachers' use of DI on students' mathematics and reading achievement (Bal, 2016;Goddard et al, 2015;Reis et al, 2011). Furthermore, studies by Lindner et al (2021) and Pozas et al (2021) indicate that students' perceptions of their teachers' DI use strongly predicted students' well-being, social inclusion and academic self-concept. Likewise, DI has also been reported to foster learners' interest, motivation and self-confidence (Eysink et al, 2017;McQuarrie & McRae, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that teachers' use of DI may have an impact on students' socio-emotional development, teachers infrequently differentiate their instruction (Pozas et al, 2021). As a result of inconsistency, it is impossible to identify whether all groups of students, including low-achieving students, benefit from DI implementation (Pozas et al, 2021). Contradictive to the previous statement, the gap between low-and high-achieving pupils should narrow as a result of DI practise (Smale-Jacobse et al, 2019).…”
Section: Practice In Secondary Educationmentioning
confidence: 99%
“…However, teachers find implementing differentiated instruction less possible due to the scarcity of materials and resources (Haelermans, 2022;Pozas et al, 2022). Despite the fact that teachers' use of DI may have an impact on students' socio-emotional development, teachers infrequently differentiate their instruction (Pozas et al, 2021). As a result of inconsistency, it is impossible to identify whether all groups of students, including low-achieving students, benefit from DI implementation (Pozas et al, 2021).…”
Section: Practice In Secondary Educationmentioning
confidence: 99%
“…Thus, more longitudinal research is needed in order to explore changes across school types, transitions, and inclusive education. Additionally, future work should consider that differences between private and public schools when it comes to inclusive education (Pozas et al, 2021). Thus, future investigations should aim to follow research designs and samples that explore nested structures.…”
Section: Limitations and Considerations For Further Researchmentioning
confidence: 99%